The EFFECT OF USING AI-POWERED CHATBOTS ON STUDENTS' SELF-REGULATED LEARNING - Nur Eva Yanti (journal Informatika, Multimedia, dan Informasi, 2025)
This study aims to examine the influence of AI-based chatbot utilization on students’ self-directed learning. The background of this research arises from the increasing adoption of Artificial Intelligence in higher education, particularly chatbots such as ChatGPT, which provide real-time explanations, instant feedback, and personalized learning support. A quantitative approach with a correlational design was employed. The sample consisted of 50 students selected through purposive sampling, and data were collected using an online questionnaire. The data were analyzed using descriptive statistics, normality tests, Pearson correlation, and simple linear regression. The results indicate that both the level of AI chatbot utilization and students’ self-directed learning fall into the moderate category. Pearson correlation analysis shows a very strong and significant relationship between AI chatbot use and self-directed learning (r = 0.836; p < 0.01). Simple linear regression further confirms that AI chatbot utilization has a positive and significant effect on self-directed learning (B = 0.718; p = 0.000). These findings suggest that AI-based chatbots play an important role as learning tools that enhance students’ ability to learn independently. The study recommends strengthening AI literacy, providing ethical use guidelines, and integrating chatbots into the digital learning ecosystem in higher education.